Supra Soft Somewhat Open Sets: Characterizations and Continuity (European Journal of Pure and Applied Mathematics, 2025)
In this manuscript, we used the supra soft interior operator to define a new approach of generalized sets named, supra soft somewhat  (briefly, SS-sw-) open sets. We discuss its relationships with the other generalizations and provide the necessary examples and counterexamples. After that, we define new continuity inspired by this new approach, named SS-sw-continuous function. We characterize several  of its essential properties.  We use the  SS-sw-closure (interior) operators to present several equivalent conditions for the  new approach. Furthermore, we define a new type of functions related  to  SS-sw-open sets, named  SS-sw-open functions.
Keywords: Supra soft somewhat open sets; SS-sw-closure operator; SS-sw-continuous functions